Children and youth speak for themselves - Johnson, Heather Beth, 1972- (Bingley, UK : Emerald, 2010)
The theme of this volume is an outgrowth of one of the Section sponsored sessions at the 2006 ASA meetings in Montreal; "Children and Youth Speak for Themselves." The volume is a collection of articles from scholars who pay particular attention to children and/or adolescents' voices, interpretations, perspectives, and experiences within specific social and cultural contexts. Contributions include research stemming from a broad spectrum of methodological and theoretical orientations. This is a cutting-edge compilation of the most current child-centred scholarship on the sociology of children and childhood.
Scholars giving voice so that children and youth can speak for themselves: an introduction to this special volume / Heather Beth Johnson -- Section I: Children's Perspectives: Perceptions, Stigmas, and Stereotypes. "They don't wanna get their education" / Susan Rakosi Rosenbloom ; "And no flowers grow there and stuff": young children's social representations of poverty / Judith Chafel and Carin Neitzel ; "I like being intervieeeeeeewed!": kids' perspectives on participating in social research / Margaret Ann Hagerman ; You can't count on nobody in life: homeless youth and the transition to adulthood / Laura J. Napolitano ; Child sexual abuse and embodiment / Heather R. Hlavka ; How maltreatment matters: effects of childhood maltreatment on academic performance / Daniel Jason Potter -- Section II: Exploring Children's Creative Processes. The importance of audience and agency for representation: a case study of an urban youth media community / Linda Charmaraman ; From "He's too nice" to "Some day": using photography to understand what urban students want to learn in school / Kristien Zenkov -- Section III: Students' Perceptions on Education and Activities. Middle school students' perceptions of character education: what they are doing when someone is looking / Suzanne S. Hudd ; The value of volunteering: comparing youths' experiences to popular claims / Sandi Kawecka Nenga ; Trophies, tears, and triumphs: children's experiences in competitive activities / Hilary Levey ; "Into it" or "Going through the motions": exploring how college students' understand their academic engagement / Jeff Lashbrook ; Moving into line: the educational, occupational, and family ambitions of the youth of Gautreaux Two / Melody L. Boyd and Kimberly A. Goyette -- Section IV: Racial Attitudes and Race Awareness among Children. Speaking the unspeakable: youth discourses on racial importance in school / R. L'Heureux Lewis ; "I learn being black from everywhere I go": color blindness, travel, and the formation of racial attitudes among African American adolescents / Erin N. Winkler.
Description based on print version record.
Print version record
Keywords: Group values (Sociology) in children; Socialization; Educational sociology; Child psychology; Sociology; Social issues (Children's/YA); Social Science -- General; Social Science -- Sociology -- General; Social Science -- Children's Studies